2001
DOI: 10.1046/j.1365-2672.2001.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing attachment of thermophilic bacilli to stainless steel

Abstract: Aims: This project aimed to investigate the mechanism of attachment of the vegetative cells and spores of thermophilic bacilli to stainless steel with a view to devising strategies to limit bio®lm development and survival. Methods and Results: Spores and vegetative cells of bacterial isolates were exposed to protein denaturing agents (sodium dodecyl sulphate (SDS) and trypsin) and polysaccharide removing agents (sodium metaperiodate, trichloroacetic acid (TCA) and lysozyme). Treatment with sodium metaperiodate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
95
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 27 publications
(32 reference statements)
1
95
1
6
Order By: Relevance
“…Flint et al (10) showed that attachment of bacteria can be inhibited by whole milk but can also be enhanced by the presence of lactose and noncasein protein solutions. Milk proteins have been found to decrease attachment of both vegetative cells and spores of thermophilic bacilli (27). Our study revealed small amounts of submerged B. cereus biofilms.…”
Section: Discussionmentioning
confidence: 55%
“…Flint et al (10) showed that attachment of bacteria can be inhibited by whole milk but can also be enhanced by the presence of lactose and noncasein protein solutions. Milk proteins have been found to decrease attachment of both vegetative cells and spores of thermophilic bacilli (27). Our study revealed small amounts of submerged B. cereus biofilms.…”
Section: Discussionmentioning
confidence: 55%
“…DSF regulation of exopolysaccharide production may also contribute to virulence and transmission in X. fastidiosa. In some systems, exopolysaccharides inhibit cells from forming initial, specific attachments required for biofilm formation, perhaps by masking attachment proteins (34,35). In other cases, exopolysaccharide synthesis enhances biofilm formation (36,37), perhaps at postattachment steps.…”
Section: Discussionmentioning
confidence: 99%
“…Surface growth causes various negative effects in many technical systems, and different means to eliminate, reduce, and control the formation of biofilms have been suggested (4,11,29,30). One of the areas where problems with biofilm growth are rather severe is in pulp and paper mills.…”
Section: Discussionmentioning
confidence: 99%